Simulation of Optical Waveguide on Communication Signal Wave Delivery Between Airplane and Airport Through Tower - Raya, Al Gibran; Rahmah, Aulia; Izzati, Revieana Dzil; Zalianty, Salwa Xenia; Firmansyah, Firmansyah (MJI Publisher by PT Mitra Jurnal Indonesia, 2024)
Optical waveguides have become essential in modern telecommunications and sensor technologies, offering light confinement and guidance efficiency. This article provides a comprehensive review of recent advances in the application of optical waveguides to aircraft sensors in sending navigation signals to airport signal-receiving towers, taking into account comparisons based on the GLB (regular straight motion) formula to determine how fast the time for signals from FAA and ICAO moves in units of seconds. Calculation of the signal time to the tower by comparing the maximum distance traveled with the average signal speed, the advantage of signal speed can be utilized by companies to display products and expand products owned by aviation companies to get additional benefits. In this case, there are several things that we examine with the method: (1) Searching for comparative reference data between FAA and ICAO, (2) Collecting additional data on FAA user companies that will expand, (3) Calculating the speed comparison between FAA and ICAO, (4) Visualizing supporting company data to ascertain whether the company has healthy finances to expand, In this case the comparison of signal speeds carried out by each aircraft to each tower to prepare a framework that can be used to support the company's expansion. Considering several possible factors that will occur if business expansion is carried out, this simulation examines the transmission of communication wave signals between aircraft and airports through towers using optical waveguides. The simulation results show that optical waveguides can send communication signals between airplanes and airports safely and efficiently.